Hubungan Kedekatan Keluarga dengan Konsep Diri Remaja Putri di Panti Asuhan Al Islam, Sleman, Yogyakarta - Nasiatul Aisyah Salim; Antok Nurwidi Antara (Yayasan Literasi Sains Indonesia, 2022)
Adolescene is a critical period of development. Adolescents face a period of searching for answers to questions about themselves. So that adolescence is an important period in the formation of self concept. Parents are the earliest social contact experienced by a person and the most powerful in the formation of self concept. However, some teenagers are faced with the choice of having to separate from their families and live in orphanages. Several psychological problems are experienced by adolescents who live in orphanages so that it will affect the process of forming adolescent self concepts. This study aims to determine the relationship between the closeness of parents with the self concept of young women with the type of research that is observational analytic with cross sectional study design. The number of samples as many as 18 people with a sampling technique that is total sampling. Sampling using a questionnaire and data analysis using the chi square test. The result of this study indicate that self concept and family closeness in the good category is 61,1 %. However, the results of data analysis showed that there was no relationship between family closeness and self concept (0,24). It is hoped that the young women of the orphanage can socialize and easily get along with the environment in order to further increase their self confidence so that their self concept will be better.